Design and in-vitro evaluation of mouth dissolving tablets of olanzapine - Maheswarappa, Manjunatha Kattalagere; Desai, Priyankabahen Dineshchandra (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of the present investigation was to formulate mouth dissolving tablets of olanzapine, an anti-psychotic drug.Mouth dissolving tablets (MDT) of Olanzapine were prepared with the addition of different superdisintegrants, namely, crospovidone, croscarmellose sodium, and sodium starch glycolate. Each of these superdisintegrants was used in concentrations of 2% w/w, 4% w/w, 6% w/w, and 8% w/w. Formulation with 4% w/w crospovidone showed minimum disintegration time (<30 seconds). Furthermore, increasing the concentration of the superdisintegrants did not decrease the disintegration time (DT) significantly, so the same formulation was selected to incorporate the effervescent agent to reduce the disintegration time further. The formulation was optimized successfully with sodium bicarbonate and citric acid (monohydrate) as the effervescent agent, with 4% of crospovidone, thereby reducing the disintegration time to 10 seconds. The prepared batches were evaluated for organoleptic properties, hardness, friability, weight variation, in-vitro disintegration time, in-vitro dispersion time, wetting time, in-vitro drug release studies, and stability studies.The drug-excipient interaction was studied by Fourier transform infrared spectroscopy (FTIR) studies. The optimized formulation showed minimum disintegration time (10 seconds) and an almost complete release of the drug within five minutes. Finally it was concluded that the MDT of Olanzapine could be successfully formulated by adding superdisintegrants and an effervescent agent, with improved patient compliance.